Concerning ecclesiology: Four barriers preventing insider movement contextualization from producing biblical churches - Bennett, Matthew Aaron (Missiology, 2020)
Contextualization is a topic of utmost importance in the field of missiology. Over the past several years, the missiological world has debated the merits of one particular approach to contextualization known as the Insider Movement (IM). While much of the discussion has focused on issues of soteriology, hermeneutics, theology of religions, and evangelism, this article intends to assess the potential for IM strategies to produce biblically faithful churches. By leaning on the writings of IM advocates and the recent publication of Jan Prenger’s dissertation, Muslim Insider Christ Followers, one can compare IM strategies along with the testimony of insiders themselves with biblical teaching regarding the church. In order to avoid the accusation of historical, doctrinal, or extra-biblical imposition on the biblical teaching of the church, the common historical marks of the church have not been selected as the criteria for assessment. Instead, four biblical passages containing teaching about the church have been selected drive this exploration exegetically: (1) the church built upon the common recognition of Jesus as the awaited Messiah and Son of God; (2) the church as local, identifiable, gatherable, and responsible body of believers; (3) the church as a pillar and buttress of the truth; and (4) the church as an indiscriminate gathering of gospel-professing and communally covenanted believers. Upon considering the texts that drive these four elements of biblical churches, one confronts several barriers that often attend IM strategies. If such barriers are not removed by IM proponents, this article concludes that it is unlikely that they can produce healthy and biblically faithful churches.